Government Credit Guarantees, Financing Access, and Innovation in Chinese Tech-Based Enterprises - Zhou Yuze (SHS Web of Conferences)
Technology-driven small and medium enterprises (SMEs) in China are key to innovation but often struggle to obtain bank financing due to information asymmetry and lack of collateral. This study examines how government-backed credit guarantee programs affect these firms’ financing access and innovation output, using firm-level panel data from Chinese tech-based SMEs over 2018–2020. Amid a policy push for technological self-reliance, the author employ a difference-in-differences model with firm and year fixed effects to identify the causal impact of guarantees. The author find that government guarantees substantially improve credit availability— raising loan approval rates and loan amounts—by partially underwriting lender risk. This enhanced financing, in turn, is channeled into greater innovation: firms with guarantees increase their R&D investment and patent output compared to similar firms without guarantees. The mechanism lies in alleviating credit constraints: guarantees mitigate banks’ risk aversion and signal firm creditworthiness, enabling startups to secure affordable capital for innovation. Overall, government credit guarantees serve as an effective policy tool to bridge financing gaps and stimulate innovation-driven growth among Chinese tech enterprises.